Manajemen Kurikulum - Rizki Aulia Syahfitri; Qisti Aqila Rahma; Dedik Dedik (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Curriculum management is a fundamental aspect in the education system that integrates all components of learning to achieve educational goals effectively and efficiently. This article aims to examine the concept, principles, and implementation of curriculum management and evaluate the challenges faced in practice in educational units. With a qualitative approach based on literature studies, this study found that good curriculum management is based on the principles of productivity, democratization, efficiency, and stakeholder involvement. However, obstacles such as lack of teacher competence, limited facilities, and lack of understanding of the curriculum are the main obstacles. Therefore, evaluation and strengthening of teacher capacity and provision of facilities are strategic steps in improving the quality of education through adaptive and contextual curriculum management.